DIRECTIONS FOR FORMING A COMPETITIVE DEVELOPMENT STRATEGY OF HIGHER EDUCATION INSTITUTIONS - SHPILEVA, Vira; DIBRIVKA, Andrii; PONOMARENKO, Ahjela (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The modern higher education system is undergoing profound transformations driven by globalization, digitalization, demographic changes, and labor market dynamics. Under these conditions, higher education institutions (HEIs) must not only ensure stable functioning but also develop effective development strategies capable of maintaining competitiveness at both national and international levels. Increasing competition for applicants, academic staff, and financial resources requires flexible management solutions focused on improving the quality of educational services, fostering innovation, strengthening international partnerships, and building a strong university brand. This issue is particularly relevant for Ukrainian HEIs, which operate under conditions of economic instability, wartime challenges, and the need for integration into the European Higher Education Area. According to the Strategy for the Development of Higher Education in Ukraine for 2021–2031, the key priorities include digitalization, internationalization, scientific development, and financial sustainability — all of which determine the global competitiveness of universities. This highlights the urgent need to develop theoretical and practical approaches to forming a university development strategy aligned with contemporary global trends. However, challenges remain in the effective use of strategic management tools such as the Balanced Scorecard, KPI systems, and benchmarking, as well as in establishing stronger cooperation with businesses and public institutions. The gap between theoretical approaches to competitiveness management and their practical implementation reduces the potential of Ukrainian universities in the global educational environment. The purpose of this study is to substantiate the theoretical foundations and develop a competitive strategy for the development of higher education institutions, taking into account global trends and national specificities. University competitiveness encompasses the quality of educational programs, academic potential, the level of digitalization, financial stability, international cooperation, and reputational capital. Strategic directions for its enhancement include digital transformation, internationalization, innovation, and branding, which contribute to the harmonization of Ukrainian higher education with European standards. Thus, the competitiveness of universities is a multifactorial category requiring a systematic approach and the synergy of internal resources and external opportunities. Strengthening it ensures sustainable development and successful integration of Ukraine into the global educational and scientific space.